An Analysis of the use of the Car of the Traveling Library (CTL) of the Library Department of Pangkalpinang City in the Growing Interest of Students in Reading in the District of the city of Pangalpinang - Mumtaz, Wagiyah; Kesuma, Aghesna Rahmatika; Najogi, Zhafira Azfa; RA, Okta Reni Azrina (Jurnal El-Pustaka, 2023)
The Mobile Library Car (MPK) is one of the breakthrough services provided by the Pangkalpinang City Library and Archives Service in optimizing its role as an informal government institution whose function is to educate the nation's life according to the mandate of Pancasila and the 1945 Constitution. This study uses a qualitative descriptive methodology and provides convenience in this study, researchers used 3 steps in data collection, namely conducting observations, interviews and literature review. The existence of the Pangkalpinang City Library and Archives Service by providing various types of services, one of which is the Mobile Library Car (MPK) as an informal education provider institution in order to fulfill the mandate stated in the 1945 Constitution and the foundation for the formation of the Indonesian State Government, especially in the intellectual life of the nation, because every Citizens have the right to receive education both through formal and informal channels in order to develop their personal potential which aims to increase knowledge, insight and intelligence. This cannot be separated from the role and support of many parties, both the government, educational institutions and the community as stake holders